Solidarity Punk Boy Group in Porong Area - Mokhammad Ilham Fuady; Ketut Prasetyo; Nasution (The Indonesian Journal of Social Studies, 2023)
Solidarity is very important in a group, one of which is in the Punk Porong children’s group. This study explains how the form of solidarity that exists in the Porong punk group. This research will be viewed from the perspective of Solidarity proposed by Emile Durkheim. This study uses a qualitative approach with a case study design. The subjects in this study were 4 Punk Porong children. Data collection techniques through observation, interviews, and documentation. This research uses Milles and Hubbermans data analysis, model. This research strengthens Emile Durkheim’s theory of mechanical and organic solidarity. The result of this research is that the solidarity that is built in this group of Punk Porong children is 1) sharing joy. 2) Sharing is difficult and 3) things that can’t be shared